US trade wars with emerging countries in the 21st century: Make America and Its partners lose again - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
In a context of rising protectionist rhetoric, this paper looks at the potential impact of trade wars initiated by a change in US trade policies. We show that such trade wars can hurt emerging countries and damage the global trading system without bringing gains for the United States. We use a static multicountry, multisector Armington trade model to evaluate 6 modalities of 3 potential trade wars—for a total of 18 scenarios—between the United States and China, between the United States and Mexico, and between the United States and both China and Mexico. We also determine and analyze the optimal noncooperative unilateral tariff that the US government can implement against all of its trading partners. In each case, we evaluate various forms of trade retaliation by the trading partner(s): the same level of import duty as the one imposed by the United States, a duty that minimizes welfare loss, a duty that minimizes terms-of-trade deterioration, a duty that generates the same amount of collected revenue, and finally, a Nash equilibrium. We conclude that there is no scenario in which the US government augments its domestic welfare or gross domestic product. There may be sectoral gains in value-added in the United States, but they are small and to the detriment of other sectors. Although losses for China are relatively small, potential losses for the Mexican economy are significant. There are also potential free riders of these trade wars, particularly in Central America. Finally, the way in which trade retaliations are designed matters greatly.